Relatório de estágio técnico profissional em medicina veterinária: reprodução animal - Mazzarollo, Helen Brandalise (2023)
During the Supervised Professional Technical Internship (ETPS), it was possible to improve and put into practice all the theoretical knowledge acquired during the Veterinary Medicine degree, in the area intended for professional practice. The ETPS was carried out in the area of ​​reproduction and reproductive biotechnology, an area of ​​interest for the intern, under the academic guidance of Professor Fernando Pilotto. The ETPS was carried out at the company Biotec Serviços de Apoio à Pecuária, located in the city of Nova Prata, Rio Grande do Sul, from July 24, 2023 to October 30, 2023, totaling 546 hours, with local supervision by Veterinary Doctor Monique Frata. Through ETPS, it was possible to experience the laboratory and field routine, accompanying veterinarians and laboratory technicians in the complete process of producing bovine embryos in vitro, packaging for Direct Transfer (DT) freezing, or for fresh transfer, follicular aspiration, conventional embryo collection and thawed embryo transfer. This report includes a description of the internship location and the activities monitored during this period, which are divided between sectors and individual stages of production. At the end, a case of contamination in fertilization plates, cultivation and medium tubes for in vitro maturation of oocytes will be reported. As a result, the supervised professional technical internship was fundamental for professional and personal maturity, through the opportunity to experience experiences within the laboratory and in the field. Getting to know the laboratory routine, interacting with different people, as well as following specialized sectors and professionals enriched the academic's vision of the future of the profession as a Veterinary Doctor.